1987
DOI: 10.1093/nar/15.8.3625
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal variations in Candida albicans

Abstract: We report here the separation of chromosomal DNA molecules from the diploid pathogenic yeast C. albicans by field inversion gel electrophoresis (FIGE)(1). Our earlier work on C. albicans ATCC strain 10261 revealed a pulsed field gel electrophoretic pattern of six bands, two of which were possibly doublets (2). In the present study we found that FIGE gave superior resolution with uniform DNA mobility between lanes, and therefore could be used to examine the possibility of electrophoretic karyotype variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 2 publications
1
28
0
Order By: Relevance
“…Using the first technique, we have recently presented evidence for nine separable bands in C. albicans, although in no one strain were all nine resolvable (14). Similar results were obtained by Snell et al (24,25). Since blotting of these electrophoretic karyotypes is possible (2), one can assign cloned genes to particular bands and thus, in principle, identify the electrophoretic band corresponding to a genetically determined linkage group.…”
supporting
confidence: 57%
“…Using the first technique, we have recently presented evidence for nine separable bands in C. albicans, although in no one strain were all nine resolvable (14). Similar results were obtained by Snell et al (24,25). Since blotting of these electrophoretic karyotypes is possible (2), one can assign cloned genes to particular bands and thus, in principle, identify the electrophoretic band corresponding to a genetically determined linkage group.…”
supporting
confidence: 57%
“…Kuryotypes of the Candida species Karyotypes have been analysed in C. albicans (Merz et al, 1988;Lott etal., 1987;Mahrousetal., 1990;Lasker ef al., 1989;Snell et al, 1987;Magee et al, 1988;Iwaguchi et al, 1990) (Sor & Fukuhara, 1989) and C. glabrata (Kaufmann & Merz, 1989;Asakura et al, 1991). Only C. albicans has been studied extensively.…”
Section: Piuidy Of the Candida Speciesmentioning
confidence: 99%
“…Pulsed-field electrophoresis has permitted the separation of chromosome-sized DNA molecules of many organisms including the medically important yeasts C. albicans (42,47,52,53,63,100,101), C. stellatoidea (41,53), C. tropicalis (47,53), C. guilliermondii (53), C. glabrata (34,47,53), C. utilis (18), C. shehatae (18), Cryptococcus neoformans (81), and S. cerevisiae (18,47,53,63,101) and strains of 14 other ascomycetous and basidiomycetous yeast genera (18). The striking finding has been the extent of variation in the electrophoretic karyotypes observed among C. albicans isolates.…”
Section: Electrophoretic Karyotypingmentioning
confidence: 99%
“…Magee and Magee (53) in 1987 showed that four strains had five to seven DNA bands and each strain had different electrophoretic karyotype patterns. Snell et al (100) showed that six of six strains of C. albicans studied had discernible karyotypic variation with five to seven discrete bands. Merz et al (63) showed that both the number of chromosome-sized DNA bands (seven to nine) and the patterns of the bands varied significantly.…”
Section: Electrophoretic Karyotypingmentioning
confidence: 99%